A determination of the Planck constant using the LNE Kibble balance in air. (28th June 2017) - Thomas, M; Ziane, D; Pinot, P; Karcher, R; Imanaliev, A; Dos Santos, F Pereira; Merlet, S; Piquemal, F; Espel, P
Abstract: A determination of the Planck constant h using the LNE Kibble balance in air was carried out in the spring of 2017. Substantial improvements since 2014, chiefly related to the mass standard, mechanical alignments, voltage measurements and type A evaluation uncertainties, leads to a h value of 6.626 070 41(38)  ×  10 –34 J · s, with a relative standard uncertainty of 5.7  ×  10 –8 .